Differential-drive Robot Navigation in Crowded Environments - Lanaspa Bescós, Diego; Martinez-Baselga, Diego; Montano, Luis; Riazuelo, Luis (Jornada de Jóvenes Investigadores del I3A, 2025)
The paper adapts AVOCADO for non-holonomic robots by bounding tracking error and integrating feasible velocities, ensuring safe motion under kinematic constraints.